Protective effect of ginsenoside against acute renal failure and expression of tyrosine hydroxylase in the locus coeruleus - Zhang, H. A; Wang, M; Zhou, J; Yao, Q. Y; Ma, J. M; Jiang, C. L (Physiological research, 2010)
Acute renal failure (ARF) is mainly characterized by acute tubular necrosis. No significant change was found for mortality rates over the past few decades despite significant advances in supportive care. In recent years, great effort has been focused on traditional and herbal medicine, which is much less toxic than those agents conventionally used and which is nowadays considered as a novel therapeutic agent for ARF. However, the effect of ginsenosides (GS) administered orally on ARF has not been reported yet and little is known about its cellular and molecular mechanism. The purpose of the study is to investigate the protective effect of ginsenoside in rats with ARF on the changes of tyrosine hydroxylase immunoreactivity (TH-IR) as well as on the involvement of mitogen-activated protein kinases (MAPK) in the locus coeruleus. In our assay, glycerol-induced acute renal failure in rats was employed to study the protective effects of ginsenoside. Our results indicated that the treatment of ARF rats with ginsenosides for 48 h significantly reduced the serum blood urea nitrogen, creatinine level, and lipid peroxidation, restored the GSH level and the normal renal morphology. Immunohistochemistry showed that an obvious increase of TH-IR was further enhanced in ARF+GS group. The same effect was also observed in the changes of p-ERK1/2-IR in the locus coeruleus. Our results suggest that ginsenoside administered orally may have a strong renal protective effect against glycerol-induced ARF, and ginsenoside can also activate the brain catecholaminergic neurons in the locus coeruleus. Our future attention will be focused to the question whether there is a correlation between the renal protective effect of ginsenosides against acute renal failure and the activation of tyrosine hydroxylase in the locus coeruleus.
Keywords: financování organizované; Animals; Kidney; Tyrosine 3-Monooxygenase; Water Deprivation; glutathion; biologické markery; akutní poškození ledvin; Biomarkers; Glutathione; Up-Regulation; mitogenem aktivovaná proteinkinasa 3; ginsenosidy; Glycerol; Time Factors; časové faktory; Immunohistochemistry; mitogenem aktivovaná proteinkinasa 1; upregulace; Ginsenosides; Protective Agents; dusík močoviny v krvi; imunohistochemie; tyrosin-3-monooxygenasa; peroxidace lipidů; Rats, Sprague-Dawley; Financing, Organized; Lipid Peroxidation; Male; fosforylace; modely nemocí na zvířatech; potkani Sprague-Dawley; Malondialdehyde; aplikace orální; Blood Urea Nitrogen; Mitogen-Activated Protein Kinase 3; Creatinine; Disease Models, Animal; krysa rodu Rattus; glycerol; malondialdehyd; deprivace z nedostatku vody; kreatinin; zvířata; mužské pohlaví; ochranné látky; Administration, Oral; Acute Kidney Injury; ledviny; Locus Coeruleus; Mitogen-Activated Protein Kinase 1; Rats; Phosphorylation; locus coeruleus